Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

lharrell17

  • 3 years ago

-5 – 3(x – 2) = -2.

  • This Question is Closed
  1. order
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    -3(x-2) = -2 + 5 -3x +6 = 3 -3x = 3-6 -3x = -3 x = 1

  2. RJV
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    -5 – 3(x – 2) = -2 distribute -3 to x-2 -5-3x+6=-2 transfer the numbers without literal coefficient -3x=-2-6+5 -3x=-3 x=1

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy